Donald Trump, Kebijakan Pembatasan Imigran Muslim, dan Islamophobia dalam Perspektif Sejarah Demokrasi Amerika Serikat - Yansah, Ali; Harpan Reski Mulia (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2023)
The United States is known not only for its strength in controlling economic aspects but also as a democratic country. History records American democracy as a historic achievement. However, since becoming the president of the United States in 2017, Donald Trump had a significant impact on democracy. His policies against Muslim immigrants were later assessed by observers as illegal and tarnishing the history of United States democracy. This paper explores the broad picture of Donald Trump's policies, how observers responded, and what impact it had on the history of United States democracy. Using the chronological-thematic historical method, the study found that many internal circles in the United States responded, such as Harvard Law School students who compared it with the provisions of the United States. The history of democracy in the United States is not appropriate as a fulcrum for the cause of Donald Trump's policy of eradicating Muslim Immigrants.